Escala de crenças acerca da violência sexual (versão reduzida): evidências de validade e precisão - Medeiros, Lívia Laenny Vieira Pereira de (2022)
This dissertation aimed to investigate the phenomenon of beliefs about sexual violence against women. Specifically, it seeks to present validity and reliability evidences of the Beliefs about Sexual Violence Scale (BSVS). Therefore, three studies were carried out. Study 1 (N = 231) aimed to carry out the exploratory factor analysis of the BSVS short version. Through principal axis factoring, an unifactorial organization was observed with the fifteen items (eigenvalue = 3.43; explained variance = 23%), which showed adequate reliability (α = 0.81). Study 2 (N = 231) sought to carry out the confirmatory factor analysis of the instrument. The model fit indices supported the validity of the 15-item version (χ2/df = 1.21; GFI = 0.91; CFI = 0.96; TLI = 0.96; RMSEA = 0.03 | 90% CI0.01 — 0.05|). Finally, Study 3 (N = 240) analyzed the correlations between beliefs about sexual violence and other variables of interest. Positive relationships were observed with the four factors of the Acceptance of Rape Myths Scale (woman's accountability minimization of severity; female excusesand male instinct), demonstrating the convergent validity of the instrument. Furthermore, beliefs about sexual violence were positively correlated with physical aggression, angerand the conscientiousness personality traitand negatively with openness.